Fluxes and balance of mercury in the inner Bay of Puck, southern Baltic, Poland: an overview - Leonard Boszke (Oceanologia)
The aim of the study was to analyse the balance of mercury (Hg), i.e. the content of this metal, its inflow and outflow, in the ecosystem of the Bay of Puck. Based on literature data and the results of the author's own study, this analysis has shown that the main source of Hg pollution is the atmosphere. An estimated 1.1-3.8 kg of Hg enters annually from the atmosphere, whereas the mass of Hg carried there by river waters per annum is about 7 times lower (0.13-0.44 kg year-1). The 0.9-2.7 kg year-1 of Hg released from Bay of Puck waters to the atmosphere is of the same order as the quantity deposited from the atmosphere. The total amount of Hg deposited in the upper (0-5 cm deep) layer of the sediments has been estimated at 240-320 kg, its rate of entry being c. 2.25-2.81 kg year-1. 0.25-1.25 kg year-1 of Hg are released from the bottom sediments to bulk water, while 0.61-0.97 kg remains confined in aquatic organisms, including 133 g in the phytobenthos, 2.6 g in the zooplankton, 420-781 g in the macrozoobenthos and 34 g in fish.